Remembering God and Da’wa through English Islamic Song Lyrics of Indonesian Nasyid - Maria Ulfa (Insaniyat : Journal of Islam and Humanities, 2018)
This paper examines English Islamic song lyrics from an Indonesian nasyid group named Snada. The group is known as the icon of Indonesian nasyid group. The English lyrics are their efforts to get wider audience not only from Indonesia but also from international audience. This research analyses two English song lyrics sung by Snada namely “My Pray” and “Where Are You Going” from Snada’s song albums to understand and explain more on their contents and meanings including the Islamic values, teachings, and messages as well as the functions and purposes of the Islamic lyrics related to Islamic da’wa. Both of the lyrics have similar theme in general namely remembering Allah. This qualitative-descriptive research tries to examine the lyrics by using poetry theory through some elements of poetry, da’wa concept, and by using both content analysis and comparative analysis. The analysis shows that there are some similarities and differences between the two for their literary poetical elements and also their Islamic values, teachings, messages, and functions or purposes. The Islamic da’wa is done through English song lyrics sung by Snada to get wider audience. The analysis also shows that the lyrics are about the invitation, reminder, suggestion, and persuasion to remember, love, pray to, and believe in Allah as the source for guidance in life. The da’wa messages are addressed for both Muslims and other people in general. Lastly, through English song lyrics, they have done their Islamic da’wa movement in song music to wider audience as well as for entertainment and Islamic education.DOI: 10.15408/insaniyat.v2i2.7851